Making With Place: Youth Public Art Experiments - Lombardo, Charlotte; Novak, Phyllis; Flicker, Sarah (Art/Research International, 2023)
Making With Place explores expressions and desires of queer, Indigenous, and racialized young artists on place, community, and culture. During the height of the COVID-19 pandemic (from spring 2020 to fall 2021) community-based researchers engaged in participatory arts processes with young artists, culminating in public art installations theorising evolving inquiries and ideas into place. In this paper, we showcase six artworks to exemplify three conceptions of place that emerged from this collective work: (a) place holds histories; (b) place is relational; and (c) place as a verb. We consider how learnings from this project can help to more equitably reclaim public space through (re)mapping and (re)visioning as living processes of place-making. Community arts, in public space, can inform how we create, investigate, and make place through the arts. Who does this inviting, and who is ultimately assembled, is of vital importance. Place is where we encounter each other.